Analisis Ikhtikar Terhadap Lonjakan Harga Minyak Goreng Yang Merusak Stabilitas Pasar - Garyl Nizam Bachtiar; Hidayaturohmaniya Salsabilla; Sri Wigati (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
The surge in cooking oil prices in recent periods has caused distortions in the market mechanism and disrupted the economic stability of society, especially in the household and MSME segments that heavily rely on this commodity as a staple need and production material. The unreasonable price increase has led to public anxiety and indicates structural problems in the national cooking oil trade system, ranging from market dominance by large players to weak distribution control by the government. From an Islamic economic perspective, this condition needs to be examined because it concerns the principle of public welfare (maslahah ammah) and the prohibition of exploitative practices such as hoarding or ikhtikar. Therefore, this study aims to analyze the forms of ikhtikar carried out by stakeholders and their relevance to the principles of Islamic economics in responding to this price volatility. The study uses a literature review method with a descriptive analytical approach through a review of historical price data, government policies, and fiqh muamalah literature related to market practices. The findings indicate that price fluctuations are driven by a combination of production factors, distribution, and speculative actions leading to ikhtikar. Intervention policies such as market operations, price controls, and export restrictions temporarily reduce prices in the short term, but they have not addressed structural causes such as distribution inequality and lack of transparency in the supply chain. The study concludes that the control of ikhtikar from the perspective of Islamic economics must be focused on preventing monopoly, ensuring equitable distribution, strengthening the government's supervisory role, and promoting transparency in price information to support the creation of market stability and the sustainability of public welfare.